Analisis Strategi Pembelajaran dalam Meningkatkan Pemahaman Konsep Bangun Datar di Sekolah Dasar - Safrida Napitupulu, Dalimawaty Kadir, Beta Rapita Sillalahi, Isnan Nisa Nasution, Cheisya Anastasya, (FKIP UNSULTRA, 2026)
This study aims to examine various learning methods that can improve elementary school students' understanding of plane geometry concepts using a literature review method. The basis of this study is the limited understanding of plane geometry concepts among students, which is often caused by the application of traditional teaching methods and the limited use of real-world media. Information was obtained from several national research articles published between 2020 and 2025, then analyzed qualitatively by looking for patterns, similarities, and differences in the research results. The findings indicate that active learning methods such as STAD-type Cooperative Learning, Discovery Learning, Probing Prompting, Inquiry, and Problem-Based Learning have proven effective in improving students' understanding of plane geometry concepts. In addition, the use of concrete and innovative learning media, such as geoboards, tangrams, puzzles, and RUSBADAR media based on Realistic Mathematics Education (RME), as well as approaches that emphasize local culture, have been proven to help students better understand the concepts of area, perimeter, and the characteristics of plane geometry. Active learning strategies encourage students to be directly involved through discussion, exploration, and problem-solving, in line with constructivist theory which emphasizes the formation of knowledge through learning experiences. Therefore, the implementation of various student-centered learning strategies and media is highly recommended to improve understanding of mathematical concepts at the elementary school level.